Medication‐induced obstructive uropathy and hyperprolactinemia in a pediatric patient - Kwabena Nkansah‐Amankra; Sathyanarayan Sudhanthar (Clinical Case Reports, 2019)
Abstract Hyperprolactinemia can result from a pituitary tumor or decreased dopamine levels due to compression of the pituitary stalk. Hypothyroidism, renal failure, and drug interaction need to be ruled out as a part of diagnostic evaluation. The prolactin level often indicates the etiology, but drug interaction needs to be ruled out mainly in a patient who is on multiple medications.